Demands of Expanding Populations and Development Planning Clean Air, Safe Water, Fertile Soils - Siegel, Frederic R.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
This book brings together three topics that interact to affect the quality of life on Earth. First, it examines expanding populations (and contracting ones) in regional and national contexts. Second, the book reviews the impacts of pollution on people, ecosystems and economic ventures. The rate of population increase is slowing but growth momentum is projected to carry the Earth's population from >6.6 billion in 2007 to 9.2-11 billion inhabitants by 2050. Vast numbers of today's world population, mainly in less developed or developing nations, suffer illnesses from chemical or biological pollutants in the air they breathe, the water they drink, and the foods they consume. Millions die. What then can be expected for a 50% larger population by 2050? Third, the book asserts that well-planned development projects adhering to environmental laws and with best available technologies, will reduce ecosystem pollution yet yield strong profit margins. Proactive project design will also carry social development aims such as in education, job creation, and healthcare. The text includes examples of pollution from human activities and reviews solutions to alleviate or eliminate them.
The Ecosystem and Development -- Populations: Growth, Braking, Contraction -- Population Needs for Well-Being -- The Surface/Near-Surface Atmosphere -- Water: An Essential, Limited, Renewable Resource -- Soil Formation, Quality, Sustainability -- “Green” Legislation: Now for the Future -- Proactive Planning in Industrial/Agricultural Development: Minimizing Chemical Pollution -- Remediation/Reclamation Options for Polluted Environments: Feasible or Not.
Keywords: Geochemistry; Environmental management; Water quality; Water pollution; Air pollution; Soil science; Soil conservation; Geochemistry; Environmental Management; Water Quality/Water Pollution; Atmospheric Protection/Air Quality Control/Air Pollution; Soil Science & Conservation; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution